Partitioned EOMEA-MBPT(2): an efficient N-5 scaling method for calculation of electron affinities - Dutta, Achintya Kumar; Gupta, Jitendra; Pathak, Himadri; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2014)
We present an N-5 scaling modification to the standard EOMEA-CCSD method, based on the matrix partitioning technique and perturbative approximations. The method has lower computational scaling and smaller storage requirements than the standard EOMEA-CCSD method and, therefore, can be used to calculate electron affinities of large molecules and clusters. The performance and capabilities of the new method have been benchmarked with the standard EOMEA-CCSD method, for a test set of 20 small molecules, and the average absolute deviation is only 0.03 eV. The method is further used to investigate electron affinities of DNA and RNA nucleobases, and the results are in excellent agreement with the experimental values.